2015
DOI: 10.1038/srep17910
|View full text |Cite
|
Sign up to set email alerts
|

SMARCAL1 Negatively Regulates C-Myc Transcription By Altering The Conformation Of The Promoter Region

Abstract: SMARCAL1, a member of the SWI2/SNF2 protein family, stabilizes replication forks during DNA damage. In this manuscript, we provide the first evidence that SMARCAL1 is also a transcriptional co-regulator modulating the expression of c-Myc, a transcription factor that regulates 10–15% genes in the human genome. BRG1, SMARCAL1 and RNAPII were found localized onto the c-myc promoter. When HeLa cells were serum starved, the occupancy of SMARCAL1 on the c-myc promoter increased while that of BRG1 and RNAPII decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 47 publications
2
29
0
Order By: Relevance
“…Consistent with this, we previously observed that SMARCAL1 homologues bind transcriptionally active chromatin and modulate gene expression [13]. Sharma et al (2015) recently showed that the bovine orthologue of SMARCAL1 negatively and directly regulates the transcription of MYC by altering the conformation of its promoter [34]. Alternatively, because stalled replication forks induce epigenetic changes that alter gene expression [35, 36], impedance of DNA replication fork restart by SMARCAL1 deficiency might contribute to the changes in gene expression.…”
Section: Discussionsupporting
confidence: 65%
“…Consistent with this, we previously observed that SMARCAL1 homologues bind transcriptionally active chromatin and modulate gene expression [13]. Sharma et al (2015) recently showed that the bovine orthologue of SMARCAL1 negatively and directly regulates the transcription of MYC by altering the conformation of its promoter [34]. Alternatively, because stalled replication forks induce epigenetic changes that alter gene expression [35, 36], impedance of DNA replication fork restart by SMARCAL1 deficiency might contribute to the changes in gene expression.…”
Section: Discussionsupporting
confidence: 65%
“…SMARCAL1 also has been reported to have a regulatory role in the transcription of a subset of genes (Baradaran-Heravi et al , 2012b, Sharma et al , 2015, Haokip et al , 2016, Patne et al , 2017). Specifically, SMARCAL1 was reported to directly modify the chromatin near promoter sequences to regulate gene expression especially in cells experiencing replication stress (Sharma et al , 2015, Haokip et al , 2016, Patne et al , 2017).…”
Section: Smarcal1mentioning
confidence: 99%
“…Specifically, SMARCAL1 was reported to directly modify the chromatin near promoter sequences to regulate gene expression especially in cells experiencing replication stress (Sharma et al , 2015, Haokip et al , 2016, Patne et al , 2017). However, SMARCAL1 binds DNA in a sequence independent manner and has not been found in complexes with any transcription factors or components of ATP-dependent chromatin remodeling complexes (Betous et al , 2012).…”
Section: Smarcal1mentioning
confidence: 99%
“…All cell lines were purchased from National Centre for Cell Science, Pune, India, and cultured as detailed previously [36,38]. Transfections were done RNA isolation, cDNA preparation and qPCR: Total RNA was extracted and cDNA was prepared using the established protocol [36].…”
Section: Cell Culture and Transfectionmentioning
confidence: 99%